Advance care planning participation by people with dementia: a cross-sectional survey and medical record audit. Issue Volume 12:Issue e3(2022) (3rd March 2021) - Bryant, Jamie; Sellars, Marcus; Waller, Amy; Detering, Karen; Sinclair, Craig; Ruseckaite, Rasa; White, Ben; Nolte, Linda
Abstract : Objectives: To describe among individuals with dementia: (1) self-reported awareness of, and engagement in, advance care planning; (2) presence of advance care planning documentation in the health record and (3) concordance between self-reported completion of advance care planning and presence of documentation in the health record. Methods: An Australian prospective multicentre audit and cross-sectional survey. Individuals diagnosed with dementia who were able to speak English and were judged by a healthcare provider as having decision-making capacity were recruited from self-selected hospitals, residential aged care facilities and general practices across Australia. Results: Fifty-two people with dementia completed surveys and were included. Overall, 59.6% of participants had heard about advance care planning and 55.8% had discussed advance care planning with someone, most often a family member (48.1%). While 38.5% of participants had appointed a medical substitute decision maker, only 26.9% reported that they had written down their values and preferences for future care. Concordance between self-reported completion of advance care planning and presence of documentation in the health record was low (56.8%, κ = 0.139; 57.7%, κ = 0.053). Conclusion: Effective models that promote discussion, documentation and accessible storage of advance care planning documents for people with dementia are needed.